The Place of Nicaea in Buddhist-Christian Theology - O'Leary, Joseph Stephen (Theological studies, 2025)
Several themes are as fundamental in Buddhist thinking as they are in the ancient and modern debates about the teaching of the Council of Nicaea (325). This article argues that if the interreligious dialogue urged by Vatican II had been more energetically sustained, a Buddhist-Christian conversation about the legacy of Nicaea could have been a significant ecumenical event, overcoming the monopoly of Eurocentric perspectives.